CORRELATIONS BETWEEN SYSTEMIC FEATURES AND DENTAL ABNORMALITIES IN MITRAL VALVE PROLAPSE SYNDROME - Paloma Manea; Cristina Maria Gavrilescu; Crînguţa Paraschiv; Irina Cotea; Dragoş Munteanu; Răzvan Constantin Anghel; Loredana Ursachi; Radu Andreica; Rodica Ghiuru (Romanian Society of Oral Rehabilitation, 2015)
Aim of the study To establish if dental anomalies are linked to systemic features for patients with mitral valve prolapse syndrome (MVPS). Material and methods We've compared the dental findings from 27 patients diagnosed with MVPS with the dental features from 27 patients without MVPS. Complete dental, cardiological and psychological consults were performed. Biochemical and haematological laboratory findings were followed. Electrocardiogram, echocardiogram, dental X-ray confirmed clinical diagnosis. Treatment received by patients with MVPS consisted in betablockers, dental procedures and psychological interventions. Results MVPS was associated with a higher prevalence of dental anomalies and negative impact among life quality. Conclusions Future researches could reveal algorithms for better understanding of MVPS and dental associated anomalies, with clinical and practical consequences.